2014
DOI: 10.1179/1743132814y.0000000380
|View full text |Cite
|
Sign up to set email alerts
|

Timing of stereotactic radiosurgery and surgery and wound healing in patients with spinal tumors: a systematic review and expert opinions

Abstract: Evidence to guide decisions regarding the sequence and timing of surgery and SRS with respect to wound healing is limited. Consistent reporting of wound healing complications will improve ability to develop guidelines for optimal treatment of spinal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 68 publications
0
32
2
Order By: Relevance
“…6365 The nutritional compromise observed in oncology patients may further preclude fusion occurrence. 38, 61 …”
Section: Discussionmentioning
confidence: 99%
“…6365 The nutritional compromise observed in oncology patients may further preclude fusion occurrence. 38, 61 …”
Section: Discussionmentioning
confidence: 99%
“…Wound complication rates of up to 46% have been reported when EBRT and surgery were combined less than a week apart [4]. Considering the increased application of SBRT as adjuvant radiotherapy treatment Itshayek et al [5] conducted a systematic review investigating the effect of timing of SBRT and surgical treatment on the risk of wound complications. The authors concluded that due the conformal dose distribution SBRT is likely associated with a lower risk of wound complications [5].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increased application of SBRT as adjuvant radiotherapy treatment Itshayek et al [5] conducted a systematic review investigating the effect of timing of SBRT and surgical treatment on the risk of wound complications. The authors concluded that due the conformal dose distribution SBRT is likely associated with a lower risk of wound complications [5]. Yet, considering the sensitivity of the early phases of the wound healing process in tissues exposed to radiation, a time interval of at least one week between surgery and SBRT is still recommended [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations